APPLICATION OF INCONEL 718 (IN718) FOR ADVANCED ARMOR MATERIAL AND ITS POTENTIAL IN INDONESIA DEFENSE INDUSTRY - Nyimas Aljaniah Zahra; Sovian Aritonang; Nugroho Adi Sasongko (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Indonesia is the world's largest source of nickel ore, controlling 27 percent of the global nickel market. Because of its unique physicochemical properties, such as malleability, high-temperature stability, strength, corrosion resistance, ductility, heat conductivity, and electrical conductivity, nickel is one of the most important metals in the industry. Nickel-based superalloys are commonly utilized to build hot-end components for aviation engines and gas turbines. The purpose of this study is to examine the use of Inconel 718 (IN718) for armor and its prospective development in Indonesia's military industry. The outcome demonstrates IN718's potential in the Indonesian defense industry, with the manufacturing of military aircraft gas turbines, submarines, military electric engines, and high-protection armor vehicles among its most prominent applications. Nickel may be recycled by using a nickel extraction technique like the liquid metal extraction-vacuum distillation (LME-VD), which produces no waste gas or solid and is environmentally beneficial. IN718's development is also by the government's goal of increasing the value-added of Indonesia's nickel production while minimizing environmental impact.